Photometrics of ultrafast and fast broadband electronic transient absorption spectroscopy: State of the art - Lang, Bernhard (Review of scientific instruments, 2018)
The physical limits of the photometric resolution in broadband electronic transient absorption spectroscopy are discussed together with solutions for how to reach these limits in practice. In the first part, quantitative expressions for the noise contributions to the transient absorption signal are derived and experimentally tested. Experimental approaches described in the literature are discussed and compared on this basis. Guide-lines for designing a setup are established. In the second part, a method for obtaining nearly shot-noise limited kinetics with photometric resolution of the order of 100 μOD in overall measurement times of a few minutes from femtosecond to microsecond time scale is presented. The results are discussed in view of other experiments of step-scan type which are subject to a background or to correlated noise. Finally, detailed information is provided on how to obtain transient absorption spectra where counting statistics are the sole source of noise. A method for how to suppress outliers without introducing bias is discussed. An application example is given to demonstrate the achievable signal-to-noise level and the fast acquisition time.